How does knowledge bring one to the state of immortality in early Upaniṣadic philosophy?: A new perspective on the "Magical" way of cognition - Takayama, Zenko (Religion, 2018)
The Upaniṣadic philosophers believed that acquiring certain knowledge would lead them toward a state of immortality. Merely by obtaining that knowledge, they thought people could surmount the various causes of death of the natural body. How and why did they develop and maintain this belief? To understand this, this article analyzes the difference between our views as modern humans and those of early Upaniṣadic philosophers, regarding the concepts of knowledge and death. They seem to have believed that knowing a concept meant actualizing that concept in the real world. Therefore, possessing the concept or knowledge of death guaranteed the actualized occurrence of death. This article argues that early Upaniṣadic philosophers must have thought that replacing the knowledge of death with the true knowledge of immortality would really make people immortal. In other words, to know that one is immortal truly makes one immortal. I also propose a new method of analyzing ancient thoughts.